2012
DOI: 10.1515/cclm-2011-0858
|View full text |Cite
|
Sign up to set email alerts
|

Independent validation of the Enhanced Liver Fibrosis (ELF) score in the ANRS HC EP 23 Fibrostar cohort of patients with chronic hepatitis C

Abstract: This study confirms the ELF score performance as an index to predict liver fibrosis or cirrhosis in CHC. The ELF test, using validated reagents, could be added to the health authorities approved non-invasive tests in assessing fibrosis as surrogate to liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 25 publications
4
47
0
2
Order By: Relevance
“…In this issue of Clinical Chemistry and Laboratory Medicine, Guechot and colleagues proposed an independent validation of ELF score in a large cohort of patients with chronic hepatitis C. The authors report an area under the curve of 0.78 for signifi cant fi brosis and of 0.85 for cirrhosis that is somehow in line with previous studies (11) . Moreover, they showed that the ELF score performed better than HA and slightly worse as compared to Fibrotest and Hepascore.…”
Section: Giada Sebastianisupporting
confidence: 62%
“…In this issue of Clinical Chemistry and Laboratory Medicine, Guechot and colleagues proposed an independent validation of ELF score in a large cohort of patients with chronic hepatitis C. The authors report an area under the curve of 0.78 for signifi cant fi brosis and of 0.85 for cirrhosis that is somehow in line with previous studies (11) . Moreover, they showed that the ELF score performed better than HA and slightly worse as compared to Fibrotest and Hepascore.…”
Section: Giada Sebastianisupporting
confidence: 62%
“…Liver fibrosis assessment can be performed using invasive (liver biopsy-LB) or non-invasive methods, which include elastography [1,2] or serological tests [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1997, a group of European scientists led by Rosenberg, and funded by Bayer Health care, have been seeking serum markers of liver fi brosis [6,8,28,29,30]. The program lasts for more than a decade and comes to identifying the ELF panel and is currently marketed in Europe.…”
Section: Elf Test (Known As Enhanced Liver Fi Brosis and As European mentioning
confidence: 99%
“…ELISA method was used for performing the ELF test. The results show that the ELF test is an algorithm of three biomarkers that can be used to determine the stage of hepatic fi brosis with good precision [29,30,31]. The calculation is based on age, HA, PIIINP and TIMP.…”
Section: Elf Test (Known As Enhanced Liver Fi Brosis and As European mentioning
confidence: 99%